Determining performance of blended finance projects in emerging markets - Karásková, Vendula (2023)
Current trends show that the level of SDG-related financing and investing is far less than what is needed in emerging markets (EMs), and there is a growing concern about how to close this gap. The blended finance project is one of the possible solutions to fill the financing gaps for achieving SDGs in EMs. Although prior research has stressed the importance of blended finance projects for EMs, there is no prior understanding of what factors determine the performance of blended finance projects in EMs, especially in their preparation and implementation stages. Therefore, this thesis explores the factors determining blended finance projects' performance in EMs during the preparation and implementation stages of blended finance projects. An induction-based qualitative research approach is used to analyse six interviews from four blended finance providers targeting the EMs. The research result is the Model of determinants that influence the performance of the blended finance projects in the preparation and implementation stage, including cross-cutting determinants. The findings indicate that determinants for the preparation and implementation phase influence each other. Cross-cutting determinants equally influence the performance at the preparation and implementation stages. These findings help project managers to understand the factors that can enhance or reduce the performance of blended finance projects in EMs.